Hazard identification and risk assessment on gas pipeline installation works / Dashan Sengeny - Dashan, Sengeny (2022)
Gas supply contributes to major fuel requirements for petrochemical plants, power generation, large and small industries to upkeep the operation and production to meet the consumer’s demand. To achieve that, gas pipeline construction plays an important role to provide the infrastructure for gas transportation through the pipelines to ensure uninterruptible supply. Constructing a gas pipeline involves high-risk activities such as excavation works, Horizontal Directional Drilling (HDD), lifting, confined space activities, and welding works which are required to be performed along the construction process. This activity requires serious attention for hazard identification associated with the task, performing risk assessment, and implementation of control measures to minimize the occurrence of occupational accidents. Hazard identification, Risk Assessment, and Risk Control (HIRARC) is a fundamental tool that helps to minimize and prevent accidents to take place in the workplace by cultivation a safe work system through matrix analysis which reveals the likelihood and severity of accidental occurrences. This study aims to perform hazard identification, conduct a risk assessment, and propose control measures based on the hazard and risk associated with the gas pipeline construction activities. Performing hazard identification based on the construction activities leads to several findings which can be evaluated and improved to prevent accidents. The evaluation and analysis are conducted based on the site practicability, experienced personnel opinions, and previous lesson learned. Upon risk assessment completion, a control measure is proposed according to worksite suitability. This is achieved through adaptation of several methods such as survey analysis conducted which consists of 127 respondent who is working in the gas pipeline-related construction field, site observation on actual construction practice, Fault Tree Analysis (FTA), and HIRARC form is used to identify the hazard and analyses the risk associated with the gas pipeline construction activities. Findings show that the attitude of the workers and responsibilities of the employee and management plays an important role in cultivating a safe work system. Besides that, negligence in small flaws leads to critical accidents or contributes to the main event which leads to a more severe impact. Moreover, this study also demonstrated that the involvement of management focusing on safety aspects improves the site safety practices. Safety competence personnel also ensures the worksite safety through site inspection and induction briefing is carried out on daily basis. Implementation of more comprehensive HIRARC through this study improves the site safety practices through awareness to the construction personnel which emphasizes on safety is everyone’s responsibility and working safely is the top priority.